Effect of Ratio of Pumpkin Juice with Pineapple Juice and Concentration of Gelatin on the Quality of Coconut Juice Sorbet - Naomi Bunga Claudia; Herla Rusmarilin; Lasma Nora Limbong (Universitas Sumatera Utara, 2016)
The aim of this research was to find the effect of ratio of pumpkin juice with pineapple juice and gelatin concentration on the quality of coconut juice sorbet made from the mixture of pumpkin juice with pineapple juice. This research was conducted at the Laboratory of Food Technology, Faculty of Agriculture, University of North Sumatera, Medan, using completely randomized design with two factors, i.e.: ratio of pumpkin juice with pineapple juice (S) : (20%:80%;40%:60%;60%:40%;80%:20%) and gelatin concentration (G): (0,2%;0,4%;0,6%;0,8%). Parameters analyzed were vitamin C content, total acid, total soluble solid, pH, fiber content, melting rate, score organoleptic values of colour, and texture and hedonic organoleptic values of colour, flavor, taste and texture. The results showed that the ratio of pumpkin juice with pineapple juice had highly significant effect on vitamin C content, total acid, total soluble solid, pH, fiber content, melting rate, score organoleptic values of texture and colour; had significant effect on hedonic organoleptic values of colour, and had no effect on score organoleptic values of flavor, taste and texture. The concentration of gelatin gave a highly significant effect on vitamin C content, total acid, total soluble solid, melting rate, fiber content, score organoleptic values of colour and had no significant effect on pH, score organoleptic values of texture, hedonic organoleptic values of colour, flavour, taste, and texture. The interactions between the two factors had highly significant effect on melting rate, had significant effect on total acid and fiber content, and had no significant effect on vitamin C content, total soluble solid, pH, score organoleptic values of colour, and texture, and hedonic organoleptic values of colour, flavor, and texture. The ratio of pumpkin juice with pineapple juice of (60% : 40%) and gelatin concentration of (0,6%) produced the best quality of coconut juice sorbet with more acceptable values. Keywords: Gelatin, pumpkin, pineapple, coconut juice sorbet.